Private Video Consultation Services and the Future of Primary Care - Salisbury, Chris; Quigley, Anna; Hex, Nick; Aznar, Camille (JMIR Publications, 2020)
In many countries, private companies provide primary care services based predominantly on offering video consultations via smartphones. One example is Babylon GP at Hand (BGPaH), which offers video consultations to National Health Service patients, 24 hours a day, and has grown rapidly in London over the last 3 years. The development of this type of service has been controversial, particularly in the United Kingdom, but there has been little formal published evaluation of these services in any country. This paper outlines the main controversies about the use of privately provided video consultation services for primary care and shows how they are informed by the limited evaluations that have been conducted, particularly the evaluation of BGPaH. This paper describes the advantages of these services in terms of convenience, speed of access, the ability to consult without traveling or face-to-face patient-doctor contact, and the possibility of recruiting doctors who cannot work in conventional settings or do not live near the patients. It also highlights the concerns and uncertainties about quality and safety, demand, fragmentation of care, impact on other health services, efficiency, and equity. There are questions about whether private primary care services based on video consultations have a sustainable business model and whether they will undermine other health care providers. During the recent COVID-19 pandemic, the use of video consulting has become more widespread within conventional primary care services, and this is likely to have lasting consequences for the future delivery of primary care. It is important to understand the extent to which lessons from the evaluation of BGPaH and other private services based on a video-first model are relevant to the use of video consulting within conventional general practices, and to consider the advantages and disadvantages of these developments, before video consultation-based services in primary care become more widely established.